Tensorflow-Powered Real-Time Object Detection For Vehicle, Helmet, And Number Plate Recognition" (Journal of Namibian Studies : History Politics Culture, 2023)
Safety helmet detection is important in many settings, including the workplace, the field, and the highway. In order to achieve precise and robust recognition in various and changing situations, helmet detection has been revolutionized using deep learning, in particular convolutional neural networks. By automating the process of helmet detection, organizations can improve efficiency and reduce the risks associated with non-compliance. This study proposes a novel approach leveraging deep learning techniques for the development of a robust algorithm aimed at detecting helmets and motorbikes. The utilization of deep learning methodologies has shown promising results in object recognition tasks, and this research aims to harness this potential to enhance safety and efficiency in various settings involving motorbike-related activities. The outcomes of this research endeavor are anticipated to contribute significantly to improving safety measures, traffic monitoring systems, and overall awareness in motorbike-related environments.